Analysis Of Acrylamide Monomer Formation In Refined, Bleached And Deodorised Palm Olein During Deep Frying Of French Fries - Hussein, Rabeaah (2006)
Analysis Of Acrylamide Monomer Formation In Refined, Bleached And Deodorised Palm Olein During Deep Frying Of French Fries